2020
DOI: 10.1097/bot.0000000000001714
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Thromboelastography to Detect Hypercoagulability: A Systematic Review and Meta-Analysis

Abstract: Objective: To review the current literature on the use of viscoelastic hemolytic assays, such as thromboelastography (TEG) and rotational thromboelastometry (ROTEM), during the perioperative period of patients and determine the ability of TEG and ROTEM to detect hypercoagulability and identify increased risk of the development of venous thromboembolism (VTE). Data Sources: PubMed, EMBASE, and Cochrane online databases were queried through February 11, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…This is in partial agreement with previous studies that have shown both decreased clot formation time and increased maximum amplitude [ 15 , 16 ]. A greater than normal MA has been able to predict thromboembolism in trauma and postoperatively [ 17 ]. In orthopedic trauma patients the risk of developing venous thromboembolism increases already when MA ≥ 65 mm, and further doubles if MA ≥ 72 mm [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in partial agreement with previous studies that have shown both decreased clot formation time and increased maximum amplitude [ 15 , 16 ]. A greater than normal MA has been able to predict thromboembolism in trauma and postoperatively [ 17 ]. In orthopedic trauma patients the risk of developing venous thromboembolism increases already when MA ≥ 65 mm, and further doubles if MA ≥ 72 mm [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of coagulopathy, especially hypercoagulopathy, is difficult to achieve through conventional coagulation tests, which include measurement of platelet count, activated partial thromboplastin time (APTT), prothrombin time (PT), d-dimer levels, and fibrinogen levels. Viscoelastic hemolytic assays (VHA), such as thromboelastography (TEG), (TEG®; Haemonetics Co., Braintree, MA, USA) and rotational thromboelastometry (ROTEM), (ROTEM®; TEM International FZC, Munich, Germany) are more reliable for the detection of coagulopathy than conventional coagulation tests, but are not commonly used [2].…”
mentioning
confidence: 99%
“…TEG MA values have previously been demonstrated to correlate with degree of hypercoagulability in a wide number of clinical conditions. [13]…”
Section: Discussionmentioning
confidence: 99%
“…TEG maximum amplitude (MA), a measure of clot strength accounting for platelet and fibrin contributions, has been validated as a marker of hypercoagulability in a wide range of conditions and has been found to correlate with macrothrombotic events. [13] Previous studies have defined hypercoagulability by a TEG MA ≥ 68 mm. [14] In this study we evaluated the relationship between commonly utilized laboratory parameters and hypercoagulability as represented by TEG MA.…”
Section: Introductionmentioning
confidence: 99%